Design and fabrication of pesticide pump sprayer cart - Ahmad Shawal, Mohd Amin (2012)
This final year project presented about pesticide pump sprayer cart that can carry about 36 litres of pesticide and water mixture. The objective of this project is to design and fabricate of a pesticide pump sprayer cart. This cart is suitable for a small garden area, boundary plant, or shrubs plant. This trolley use a pump to spray out the poison however how the pump work will differentiate this trolley with existing products in the market. The pump will work when the trolley is moved. Pesticides are sprayed out through two nozzles on the left and right with a sprayer shut off valve controlled. Therefore, this cart will ease the burden and ease of use for the work of poison plants.